Recent reforms in italian Civil Procedure: the process and the ADRs - Picardi, Nicolas; Santagada, Filomena (Civil Procedure Review, 2011)
The article intends to highlight some important features of the legal reforms operated in Italy in recent times, specially regarding the so-called ADRs.